Devolution and community-based natural resource management: creating space for local people to participate and benefit? - Shackleton, S.; Campbell, Bruce M.; Wollenberg, Eva Karoline; Edmunds, D. (2002)
This paper draws together evidence from a number of studies on the impacts of natural resource devolution policies in several Asian and southern African countries from the perspective of local people. Devolution outcomes are assessed in terms of who has greater benefits and decision-making authority. Factors that have influenced the devolution process are also examined.